2022
DOI: 10.1155/2022/8757656
|View full text |Cite
|
Sign up to set email alerts
|

A TRP Family Based Signature for Prognosis Prediction in Head and Neck Squamous Cell Carcinoma

Abstract: Purpose. Head and neck squamous cell carcinoma (HNSCC) is a classical type of head and neck cancers, with heterogeneous clinical outcome. This project is set out to create a robust risk signature based on TRP family genes (TFGs) for prognosis evaluation in HNSCC. Methods. Based on the HNSCC sample data from the TCGA website, we integrated expression profile of TFGs for 490 HNSCC cases. We explore the interactions among TFGs using STRING tool. The TFGs-based signature (TFBS) was created by Cox relative analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Unlike many other gene families, TRP family members have been largely overlooked in oncological studies despite their strong associations with the onset and progression of other disease types[ 22 - 24 ]. Here, TRP family gene expression profiles were analyzed for the first time in HCC, underscoring potentially important roles for these genes as mediators of oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike many other gene families, TRP family members have been largely overlooked in oncological studies despite their strong associations with the onset and progression of other disease types[ 22 - 24 ]. Here, TRP family gene expression profiles were analyzed for the first time in HCC, underscoring potentially important roles for these genes as mediators of oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the TRPM8 antagonist RQ-00203078 suppressed this activity, which suggested that stimulation of TRPM8 positively regulates MMP-9 [ 70 ]. Recent bioinformatical analysis of the HNSCC dataset from The Cancer Genome Atlas (TCGA-HNSC) indicated TRPM8 as one of the risk factors in HNSCC evolvement [ 71 ], but its main role in this type of tumorigenesis is still unknown.…”
Section: Androgen Receptors As a Potential Culprit Of Sex-related Dis...mentioning
confidence: 99%
“…Data on the 28 TRP channel genes used in this study are provided in a relevant published article. [22] We compared expression levels between HCC and non-tumorous samples and used Pearson correlation analysis to assess potential associations. We identified the corresponding HCC subtypes based on TRP channel-related genes with significant differences in expression, which were subjected to unsupervised hierarchical clustering using R 3.6.1 ConsensusClusterPlus Version 1.54.0 (http://www.bioconductor.org/packages/release/bioc/ html/ConsensusClusterPlus.html).…”
Section: Subtype Identification Based On Trp Channel Genesmentioning
confidence: 99%